Effect of Fibrinogen Concentrate vs Cryoprecipitate on Blood Component Transfusion After Cardiac Surgery - Ferry, Ferry; Hendra, Hendra (The International Journal of Medical Science and Health Research, 2024)
Background: The literature surrounding the use of fibrinogen concentrate versus cryoprecipitate in the context of cardiac surgery reveals significant insights into the efficacy and safety of these two treatment modalities for managing bleeding complications. Literature Review: The literature reviewed provides a comprehensive analysis of the efficacy and safety of fibrinogen concentrate compared to cryoprecipitate in managing bleeding complications following cardiac surgery. The systematic review by (Augusto Azevedo Maranhão Cardoso et al., 2015) establishes fibrinogen concentrate as a promising first-line treatment, emphasizing its advantages such as complete viral inactivation which reduces the risk of transfusion-related infections. This review synthesizes data from four studies involving 161 patients, indicating that fibrinogen concentrate can lead to decreased blood product usage and reduced perioperative bleeding. Conclusion: In conclusion, the reviewed literature consistently supports the use of fibrinogen concentrate as an effective and potentially safer alternative to cryoprecipitate for managing bleeding in cardiac surgery. The findings highlight its role in reducing transfusion requirements, improving patient outcomes, and offering economic advantages. However, the need for further research, particularly larger multicenter trials, is essential to validate these findings and inform clinical guidelines.